Enhanced photochromic response of ormosil-phosphotungstate nanocomposite coatings doped with TiO2 nanoparticles - Goncalves, Lidiane Patricia; Ferreira-Neto, Elias Paiva; Ullah, Sajjad; Souza, Luciana Valgas de; Elguera Ysnaga, Orlando Armando; Santos, Moliria Vieira dos [UNESP]; Lima Ribeiro, Sidney Jose [UNESP]; Rodrigues-Filho, Ubirajara Pereira (Springer, 2015)
Photochromic ormosil-phosphotungstate hybrid materials were prepared by immobilizing phosphotungstic acid, H3PW12O40, (HPW) in hybrid organic-inorganic ormosil matrices via sol-gel route, and the effect of addition of TiO2 nanoparticles (NPs) on the photochromic response of HPW was studied. For measurement of the photochromic response and the bleaching kinetics, the resulting sol-gel-derived ormosil-phosphotungstate hybrid materials with and without TiO2 NPs were coated as thin films on glass substrate by dip coating. The hybrid films were characterized by scanning electron microscopy, Fourier transform infrared absorption spectroscopy, Raman spectroscopy and X-ray fluorescence spectroscopy. The addition of small amounts of TiO2 was found to increase the photochromic response of the hybrid materials by as much as 277 % which is attributed to a possible interfacial electron transfer from the photoexcited TiO2 to HPW. These highly UV-sensitive coatings can find useful applications in UV dosimeters and smart windows. [GRAPHICS] .
Keywords: Ormosil; Hybrid materials; Phosphotungstic acid; TiO2; Photochromism